1989
DOI: 10.1071/ch9891705
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Australian Soft Corals. XLVI. New Diterpenes From a Briareum Species (Anthozoa, Octocorallia, Gorgonacea)

Abstract: The structures and relative stereochemistry of nine new briaran -based diterpenes from a Briareum species have been deduced from 2-D n.m.r. experiments at high field, and nuclear Overhauser effect experiments. The new compounds are (1R*2R*,3R*,5Z,7S*,8S*,9S*,10S*,11R*,-12S*,14S*,17R*)-2,3,14-triacetoxy-8,17:11,12-bisepoxy-9-hydroxybriar-5-en-18-one (5), (1R* ,2R* ,3R* ,5Z*,7S*,8S* ,9S*,10S*,11R*,12S*, 14S*, 17R*)-3,14-diacetoxy-2-butyryloxy-8,17:11,12-bisepoxy-9-hydroxybriar-5-en-18-one (6),(1R*,2R*,3R*,5Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
37
0
1

Year Published

1991
1991
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 0 publications
9
37
0
1
Order By: Relevance
“…As a matter of interest, the compounds formulated as 10 and 12 in this investigation appear to be spectroscopically identical to a pair of natural products isolated by Bowden et al from an Australian Briareum species for which structures 13 and 14 were assigned. 15 , respectively, indicating that both congeneric pairs are enantiomeric. As there are noticeable structural differences between the proposed molecular formulas for 10 and 13 (and 12 and 14), it seems conceivable that structures 13 and 14 were misformulated and that these compounds' structural assignments require revision.…”
Section: Resultsmentioning
confidence: 99%
“…As a matter of interest, the compounds formulated as 10 and 12 in this investigation appear to be spectroscopically identical to a pair of natural products isolated by Bowden et al from an Australian Briareum species for which structures 13 and 14 were assigned. 15 , respectively, indicating that both congeneric pairs are enantiomeric. As there are noticeable structural differences between the proposed molecular formulas for 10 and 13 (and 12 and 14), it seems conceivable that structures 13 and 14 were misformulated and that these compounds' structural assignments require revision.…”
Section: Resultsmentioning
confidence: 99%
“…Its 13 C NMR spectrum indicated that a γ-lactone and an ester were present, as carbonyl resonances were observed δ C 172.6 and 167.4, respectively ( Table 4 ). The 1 H NMR spectrum also indicated the presence of an acetate methyl (δ H 2.23, 3H × s) ( Table 4 ), and its NMR data were found to be similar to those of a known briarane analogue, (1 S *,2 S *,5 Z ,7 S *,8 S *,9 S *,10 S *,11 R *,12 R *,13 Z ,17 R *)-2,12-diacetoxy-8,17-epoxy-9-hydroxybriara-5,13-dien-18-one ( 6 ) ( Figure 1 ) [ 9 , 10 ], with the exception that the 12-acetoxy group in 6 was replaced by a hydroxy group in 4 . Based on HMBC correlations, an acetate group was concluded to be attached to C-2 in 4 , as an acetate carbonyl and an oxygen-bearing methine proton were observed at δ C 167.4 and δ H 4.83, respectively ( Table 4 ).…”
Section: Resultsmentioning
confidence: 88%
“…Additionally, the stereogenic centers of 4 were found to be the same as those of 6 , as the 1 H and 13 C NMR chemical shifts, proton-proton coupling data, and NOESY correlations of 4 and 6 matched. However, the optical rotation value of 4 ([α] +22 ( c 0.01, CHCl 3 )) was substantially different from that of 6 ([α] –44.9 ( c 0.31) [ 9 ]; [α] –42 ( c 0.3, CHCl 3 ) [ 10 ]), indicating that 4 was found to be the enantiomer of the 12-deacetoxy-12-hydroxy derivative of 6 .…”
Section: Resultsmentioning
confidence: 99%
“…Polyanthellin A has been isolated as both the dextro-and levorotatory forms from the west Pacific ocean near Australia and the Caribbean off the coast of Puerto Rico, respectively. 13,14 To our knowledge, it is the only cladiellin diterpene to carry this distinction. (-)-Polyanthellin A is reported to be an antimalarial agent.…”
Section: Scheme 1 Approaches To the Cladiellin Core Using Oxocarbeniumentioning
confidence: 99%